Evaluasi kelayakan jalur pedestrian di kawasan sekitar Manggarai sebagai penunjang konsep transit oriented development - Muhammad Faleri Febriyanto; Yohanes Karyadi Kusliansjah; Rumiati Rosaline Tobing (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
The implementation of Transit-Oriented Development (TOD) concept on pedestrian paths in Manggarai, Jakarta, requires well-ordered pedestrian path, as an area linkage between transit facility and various functions around it. Presently, the pedestrian paths condition around Manggarai Station is still not optimal. Meanwhile, the Transit-Oriented Development concept demands compliance with the standards in its implementation. This study aims to assess the pedestrian paths feasibility in the area around Manggarai Station, based on the criteria that should be met in supporting the concept implementation process. This research applied an evaluative method through POE (Post-Occupancy Evaluation), in measuring the standards of the existing pedestrian paths and providing recommendations for the authorities. The findings are novelties in understanding the disadvantages of safety factors, physical infrastructure, shelter for the hot and rainy season, easy access to the elderly and people with disabilities, especially in linking supporting facilities. Interestingly, the pedestrian path has an attraction that triggers people to walk a long distance with ease. Also, these findings are important in designing Transit-Oriented Development at Manggarai, such as wide sidewalks, providing zebra crossings, and trees. In addition, these result are in the form of suggestions for improving pedestrian path conditions as well as providing action plans for stakeholders.